2004
DOI: 10.1002/ppul.20129
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking does not increase hydrogen peroxide (H2O2) levels in exhaled breath condensate in 9-year-old healthy children

Abstract: Environmental tobacco smoke, also called passive smoking, was shown to have adverse effects on the health of children. Hydrogen peroxide (H2O2) is proposed as a sensitive marker of oxidative injury and inflammatory processes in the airways, being increased in adult active cigarette smokers. We tested whether passive smoking had an influence on H2O2 exhalation in healthy children. Thirty healthy passive smoking and 24 nonexposed healthy children aged 9 years were included in the study. Exhaled breath condensate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Therefore, we believe that H 2 O 2 levels do not reflect changes in airway caliber despite the fact that H 2 O 2 induces contraction of respiratory smooth muscles [38]. Our findings are in agreement with prior reports showing no correlation between FEV 1 and H 2 O 2 both in healthy [39] and asthmatic children [15] as well as in adults [16]. On the contrary, Loukides et al [10] found a significant inverse correlation between FEV 1 values and H 2 O 2 levels in steroid-naive adults with moderate asthma but not in those treated with inhaled steroids.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, we believe that H 2 O 2 levels do not reflect changes in airway caliber despite the fact that H 2 O 2 induces contraction of respiratory smooth muscles [38]. Our findings are in agreement with prior reports showing no correlation between FEV 1 and H 2 O 2 both in healthy [39] and asthmatic children [15] as well as in adults [16]. On the contrary, Loukides et al [10] found a significant inverse correlation between FEV 1 values and H 2 O 2 levels in steroid-naive adults with moderate asthma but not in those treated with inhaled steroids.…”
Section: Discussionsupporting
confidence: 83%
“…Similar issues are described by Doniec and co-workers who studied effects of passive smoking on EBC H 2 O 2 in 9 year old children [34]. They were unable to demonstrate a difference in EBC H 2 O 2 between exposed and non-exposed children, though commented that low sensitivity of the assay, and wide spread of measured concentrations of H 2 O 2 might mask subtle effects on airway inflammation.…”
Section: Discussionmentioning
confidence: 62%
“…After a 1h experimental exposure to ETS, healthy young adults had significantly higher levels of H 2 O 2 in EBC (Kostikas et al, 2013). In another study, healthy children who had one or two parents who were smokers did not have significantly higher levels of H 2 O 2 in EBC when compared to children who were not exposed to ETS (Doniec et al, 2005). BC exposure might also be the more important contributor to oxidative stress, explaining the lack of any statically significant association.…”
Section: Discussionmentioning
confidence: 99%